2007
DOI: 10.1111/j.1464-410x.2007.07093.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ciprofloxacin or trimethoprim reduces bacteriuria after flexible cystoscopy

Abstract: OBJECTIVE To report a large prospective, pragmatic, double‐blind randomized controlled trial to determine whether oral prophylactic antibiotics reduce the risk of bacteriuria after flexible cystoscopy (FC), as up to 10% of patients develop urinary infection afterwards, with significant morbidity and costs for health services. PATIENTS AND METHODS In all, 2481 patients were recruited into a three‐arm placebo controlled trial and 2083 completed it. Patients were randomly assigned to one of three treatments; (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 9 publications
4
49
0
7
Order By: Relevance
“…The positive culture from the decontaminating tray is unlikely to be of any clinical significance and probably represented contamination. The number of UTIs was consistent with known data from other studies and showed no association with disinfection type [6]. The adverse events noted were expected and typical after flexible cystoscopy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The positive culture from the decontaminating tray is unlikely to be of any clinical significance and probably represented contamination. The number of UTIs was consistent with known data from other studies and showed no association with disinfection type [6]. The adverse events noted were expected and typical after flexible cystoscopy.…”
Section: Discussionsupporting
confidence: 79%
“…This endpoint was judged to be the least sensitive (and therefore requiring the largest sample size) of the patient-related outcomes in this setting. The calculation was based on data that suggested that the rate of UTIs after cystoscopy was between 2% and 10% [6]. We assumed a UTI rate after cystoscopy of 2.5% for Cidex OPA, therefore if the rate for Tristel Fuse is Յ5% then there would be an 80% chance that the upper limit on the 95% one-tailed CI of the difference would be <10%.…”
Section: Sample Sizementioning
confidence: 99%
“…La infección urinaria y la presencia de bacteriuria es poco frecuente tras la cistoscopia flexible 7 y existe una baja incidencia de bacteriuria 8 , a pesar de lo cual, diferentes autores analizan el papel de la profilaxis antibiótica en la realización de este procedimiento. Alguno de esos estudios defienden que el uso de ciprofloxacino como profilaxis reduce significativamente la bacteriuria frente a placebo y a trimetoprim 6 , mientras que otros no observan diferencias en el uso o no de profilaxis antibiótica 9,10 . El estudio de Johnson et al 6 demuestra que la administración de 1 hora antes de la cistoscopia flexible de 500 mg de ciprofloxacino reduce de forma significativa la bacteriuria frente a placebo y frente a trimetoprim.…”
Section: Discussionunclassified
“…Alguno de esos estudios defienden que el uso de ciprofloxacino como profilaxis reduce significativamente la bacteriuria frente a placebo y a trimetoprim 6 , mientras que otros no observan diferencias en el uso o no de profilaxis antibiótica 9,10 . El estudio de Johnson et al 6 demuestra que la administración de 1 hora antes de la cistoscopia flexible de 500 mg de ciprofloxacino reduce de forma significativa la bacteriuria frente a placebo y frente a trimetoprim. En nuestro estudio observamos que ciprofloxacino 500 mg administrado una hora antes del procedimiento ni reduce ni evita la aparición de síntomas de infección urinaria, bacteriuria o asistencia a Profilaxis antibiótica y cistoscopia flexible -M. del C. Cano-García et al figura 1.…”
Section: Discussionunclassified
See 1 more Smart Citation